2022
DOI: 10.1126/scitranslmed.aba4380
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin mutant myeloproliferative neoplasms induce MHC-I skewing, which can be overcome by an optimized peptide cancer vaccine

Abstract: The majority of JAK2 V617F -negative myeloproliferative neoplasms (MPNs) have disease-initiating frameshift mutations in calreticulin ( CALR ), resulting in a common carboxyl-terminal mutant fragment (CALR MUT ), representing an attractive source of neoantigens for cancer vaccines. However, studies have shown that CALR MUT -specific T cells are rare in patients with CALR MUT MPN for unknown r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…This suggests that immune-mediated clearance by individuals expressing a mutant CALR neo-epitope high-affinity binding MHC-I allele occurs such that CALR -mutant MPN may not manifest clinically in these individuals. 140 In the first vaccine trial with a mutant CALR peptide, none of the 10 patients had any clinical response and only 2 had a CD8 + T-cell response, consistent with impaired MHC processing and/or presentation of neoepitope antigens. 145 Alternative approaches to enhance the mutant CALR-directed T-cell immune response include the use of a modified vaccine approach, such as heteroclitic peptides, which optimize MHC-I binding affinity, 140 or combination approaches with an MPN-directed neoantigen vaccine plus an immune checkpoint inhibitor, which is the focus of a recently opened phase 1 clinical trial (# NCT05444530 ).…”
Section: Calr-mutated Mpns Provide Novel Therapeutic Targetsmentioning
confidence: 96%
See 1 more Smart Citation
“…This suggests that immune-mediated clearance by individuals expressing a mutant CALR neo-epitope high-affinity binding MHC-I allele occurs such that CALR -mutant MPN may not manifest clinically in these individuals. 140 In the first vaccine trial with a mutant CALR peptide, none of the 10 patients had any clinical response and only 2 had a CD8 + T-cell response, consistent with impaired MHC processing and/or presentation of neoepitope antigens. 145 Alternative approaches to enhance the mutant CALR-directed T-cell immune response include the use of a modified vaccine approach, such as heteroclitic peptides, which optimize MHC-I binding affinity, 140 or combination approaches with an MPN-directed neoantigen vaccine plus an immune checkpoint inhibitor, which is the focus of a recently opened phase 1 clinical trial (# NCT05444530 ).…”
Section: Calr-mutated Mpns Provide Novel Therapeutic Targetsmentioning
confidence: 96%
“…Using in silico approaches, it has been shown that the mutant-specific C-terminus of mutant CALR is predicted to generate multiple neoepitopes that bind to major histocompatibility class I (MHC-I) with high affinity. 140 This has led to interest in developing T-cell receptor–mediated immune therapy, including vaccination approaches ( Figure 1 D). However, peptide-stimulated T-cell responses against mutant CALR epitopes are decreased in patients with MPN compared with those in healthy control subjects, suggesting defects in immune response and/or antigen presentation in MPN.…”
Section: Calr-mutated Mpns Provide Novel Therapeutic Targetsmentioning
confidence: 99%
“…On the other hand, six MHC class I alleles, HLA‐A*11:01, HLA‐B*08:01, HLA‐B*44:02, HLA‐C*07:01, HLA‐C*07:02 and HLA‐C*06:02, predicted as strong binders of mutant CRT‐derived peptides were underrepresented in both cohorts. 88 MHC class I skewing was specifically observed in CRT‐mutated MPNs. Pre‐stimulation of healthy donor PBMCs or pre‐immunization of mice with modified peptide sequences (heteroclitic peptides) could induce immune activation to an otherwise weak binding peptide.…”
Section: Mhc Class I Antigen Presentation and T Cell Activation By Mu...mentioning
confidence: 92%
“…MHC class I allele representation in MPN patients from US and Danish cohorts was biased towards allotypes exhibiting weak predicted binding affinities to mutant CRT‐derived peptide sequences. 88 HLA‐B*51:01, predicted to bind poorly to mutant CRT peptides, was found to be overrepresented. On the other hand, six MHC class I alleles, HLA‐A*11:01, HLA‐B*08:01, HLA‐B*44:02, HLA‐C*07:01, HLA‐C*07:02 and HLA‐C*06:02, predicted as strong binders of mutant CRT‐derived peptides were underrepresented in both cohorts.…”
Section: Mhc Class I Antigen Presentation and T Cell Activation By Mu...mentioning
confidence: 98%
See 1 more Smart Citation